2022
DOI: 10.1136/archdischild-2021-323681
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in hospital care among clinically vulnerable children aged 0–4 years during the COVID-19 pandemic

Abstract: ObjectiveTo quantify reductions in hospital care for clinically vulnerable children during the COVID-19 pandemic.DesignBirth cohort.SettingNational Health Service hospitals in England.Study populationAll children aged <5 years with a birth recorded in hospital administrative data (January 2010–March 2021).Main exposureClinical vulnerability defined by a chronic health condition, preterm birth (<37 weeks’ gestation) or low birth weight (<2500 g).Main outcomesReductions in care defined by predicted hosp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
(117 reference statements)
0
6
0
1
Order By: Relevance
“…Three papers reported on medical services for children with neurodevelopmental disabilities 17,39,40 . A study of adolescents with special educational needs used linked education, health, and social care data, which identified that a greater proportion of adolescents with special educational needs had outpatient appointments offered to them via telehealth compared to their peers 39 . One survey reported that 30.9% of follow‐up appointments for children with neurodisability with a paediatrician were carried out via telehealth 17 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three papers reported on medical services for children with neurodevelopmental disabilities 17,39,40 . A study of adolescents with special educational needs used linked education, health, and social care data, which identified that a greater proportion of adolescents with special educational needs had outpatient appointments offered to them via telehealth compared to their peers 39 . One survey reported that 30.9% of follow‐up appointments for children with neurodisability with a paediatrician were carried out via telehealth 17 …”
Section: Resultsmentioning
confidence: 99%
“…17,39,40 A study of adolescents with special educational needs used linked education, health, and social care data, which identified that a greater proportion of adolescents with special educational needs had outpatient appointments offered to them via telehealth compared to their peers. 39 One survey reported that 30.9% of follow-up appointments for children with neurodisability with a paediatrician were carried out via telehealth. 17 Two papers described successful remote telemonitoring of children and young people's ventilation and continuous EEG, reducing the need for children and young people to travel into hospital or be admitted for monitoring.…”
Section: Continuation Of In-person Appointmentsmentioning
confidence: 99%
“…Lockdowns in England affected children’s access to school and the frequency of hospital contacts captured in ECHILD data. Planned and unplanned admissions, and outpatient appointments reduced substantially during the COVID-19 pandemic, with the largest reductions in children with indicators of vulnerability (such as preterm birth, a chronic condition, recorded SEN or social care record) 12 40. School attainment measures were not collected during the pandemic to help reduce the burden on educational and care settings.…”
Section: Methods and Analysismentioning
confidence: 99%
“…3 Health care services were also disrupted by the pandemic. The drop in scheduled health care activities, urgent and emergency care services, 4,5 and hospitalizations, even for children with chronic conditions, 6 means that a number of children and adolescents who needed health care did not seek it, resulting in delays in diagnosis and treatment.…”
mentioning
confidence: 99%